Effectiveness and Safety of Isoxsuprine Hydrochloride as Tocolytic Agent in Arresting Active/Threatened Preterm Labor and Its Role in Maintenance Tocolysis: A Prospective, Open-Label Study - Jaju, Purushottam B. (American Journal of Perinatology, 2019)
Objective The aim of the study is to obtain insights on the short and long-term safety and effectiveness of isoxsuprine hydrochloride as a tocolytic agent in the management of PTL.Study Design In this prospective, single-center, noncomparative study, patients (with preterm labor at gestational age of 24–37 weeks) were administered intravenous (IV) infusion of 40-mg isoxsuprine hydrochloride until uterine quiescence, followed by intramuscular (IM) injection of isoxsuprine hydrochloride 10 mg/4-hourly for first 24 hours and maintained with retard 40-mg sustained release capsule (two times a day) till the time of delivery or 37 completed weeks of pregnancy.Results All patients (n = 50) achieved successful tocolysis in 24 hours and 48 hours postadministration of isoxsuprine hydrochloride (IV/IM/oral). Mean (±SD) gestation age at the time of delivery was 39.8 ± 2.1 weeks, with latency period of 58.5 ± 18.7 days. Pregnancy outcomes were normal in all the patients and no congenital anomaly/fetal infection was reported. Mean (±SD) fetal birth weight was 2.7 ± 0.3 kg; mean (±SD) Apgar score at 1 and 5 minutes were 7.5 ± 0.6 and 9.2 ± 0.4, respectively. Maternal tachycardia and vomiting (8.0% each) were the commonly reported adverse drug reactions, which were resolved with dose adjustment.Conclusion Isoxsuprine was found to be an effective and well-tolerated tocolytic agent in arresting PTL, in turn resulting in the overall improvement in maternal and perinatal outcomes.
Keywords: isoxsuprine; latency period; preterm labor; pregnancy prolongation; tocolytics